Technical and operational aspects of tunnel rounds in artisanal underground mining - Seccatore,Jacopo (2014)
In the world today, due to the current high price of gold, thousands of artisanal small-scale mines operate without the financial or technical capacity to upgrade their production methods, often using equipment and working methods that were forsaken decades ago in the conventional mining industry. This article illustrates, with a practical example, that it is possible to achieve the modern requirements of quality, safety and productivity, while operating with mining equipment that basically possesses the same characteristics as that employed in the 1950s. The operation involved the excavation of a 6 meter long tunnel and over 25 stoping sections in both rock and concrete by drilling and blasting in an underground gold mine. The article describes how the main operational problems were overcome. An effective drilling pattern was designed in order to be easily achievable with the limited local equipment. The behavior of the local nitrate explosive was effectively predicted and managed. The interaction with the drilling teams was managed in order to determine a meeting point between their traditional working methods and the scientific view of the engineer. At the end of the article some general guidelines are proposed for the management of similar situations, in order to improve the efficiency, productivity and safety of drill and blast operations in small-scale mines.